VERTICAL JUMP PERFORMANCE IN YOUTH VOLLEYBALL PLAYERS: AN OPTOJUMP-BASED ANALYSIS (University Arena, 2025)
Background. Vertical jump performance is a critical component in volleyball, directly involved in technical actions such as spiking and blocking. In youth athletes, understanding the neuromuscular and anthropometric determinants of jump efficiency is essential for optimizing training. Objectives: The objective of this study was to assess the biomechanical parameters of vertical jump performance (Tflight, Tcontact, Elevation, Power) in female volleyball players aged 12 to 14, and to examine their associations with anthropometric characteristics (body height and weight).Purpose: The purpose of this research was to identify the dominant physical determinants of jump efficiency in junior female volleyball players, and to provide objective support for the development of age-specific physical training programs focused on enhancing explosive strength and reducing contact time.Methods: Twenty-one athletes from the CTF Mihai I Volleyball Club participated in standardized jump testing using the OptoJump Next system. Each athlete performed three vertical jumps without arm swing. The parameters recorded were: flight time (Tflight), contact time (Tcontact), jump height (Elevation), and estimated power (Power), along with body height and weight. Spearman correlationcoefficients were used to analyze the relationships between variables.Results: Strong negative correlations were found between power and Tcontact (rs = –0.84), and moderately strong positive correlations between power and jump height (rs = 0.51). A very strong correlation was also observed between Tflight and Elevation (rs = 0.95). Anthropometric variables showed weak or moderate associations with jump performance.Conclusions: Vertical jump performance in this age group is primarily influenced by neuromuscular efficiency, rather than anthropometric characteristics. Training programs should prioritize explosive strength development and rapid force generation in volleyball-specific contexts.